Clinical development of Modified Vaccinia virus Ankara vaccines. - Gilbert, S (2013)
The smallpox vaccine Vaccinia was successfully used to eradicate smallpox, but although very effective, it was a very reactogenic vaccine and responsible for the deaths of one or two people per million vaccinated. Modified Vaccinia virus Ankara (MVA) is a replication-deficient and attenuated derivative, also used in the smallpox eradication campaign and now being developed as a recombinant viral vector to produce vaccines against infectious diseases and cancer. Many clinical trials of these new vaccines have been conducted, and the findings of these trials are reviewed here. The safety of MVA is now well documented, immunogenicity is influenced by the dose and vaccination regimen, and information on the efficacy of MVA-vectored vaccines is now beginning to accumulate.